Border detection in various levels of surround luminance. Issue 1 (January 2016) - Ishikawa, Tomoharu; Suzuki, Toshifumi; Ayama, Miyoshi
Abstract: In order to provide practical and useful data for display design, border detection with various levels of surround luminance from 0.001 to 500 cd/m 2 is investigated. The results indicated that luminance difference for border detection exhibits a monotonically increasing curve against the reference luminance on a logarithmic scale. To compare the luminance difference curves for different surround luminances, the results were converted to contrast threshold curves against the reference luminance that are U‐shaped on a logarithmic scale. These contrast thresholds, however, are higher than those of the grayscale standard display function curve. The causes of the difference between the contrast threshold curves of our study and the grayscale standard display function curve are the adaptation conditions and stimulus size, as well as the difference in criteria between the detection of a border and the detection of non‐uniformity. Finally, the necessary number of gradation levels for border detection under various surround luminances is calculated and found to be at least double the current number of levels (256). Abstract : Luminance difference for border detection with various levels of surround luminance exhibits a monotonically increasing curve against the reference luminance on a logarithmic scale and were converted to contrast threshold curves against the reference luminance that are U‐shaped on a logarithmic scale, and then, the contrast threshold curves were compared with grayscale standard display function. Finally, the necessary number of gradation levels for border detection under various surround luminances is calculated and found to be at least double the current 256 levels.